Audit related variables dan company related variables yang berkaitan audit delay dan dampaknya terhadap return saham perusahaan-perusahaan yang go public di bei - Elizabeth Sugiarto D; Yuniarwati Yuniarwati; Lerbin R Aritonang (Jurnal Akuntansi, 2011)
The obedience of Public Financial Statement to the decision of Bapepam no.Kep-36/PM/2003 have to be evaluated because it may have impact to stock prices. The objective of this research is {I) to investigate some audit related variables and company related variables that can explain or predict Audit Delay, and (2) to evaluate investor reaction of Audit Delay. The result shows that there is negative and significant investor reaction of Audit Delay, so that the company have to take attention of relevance of Public Financial Statement